Penerapan Model Pjbl Untuk Meningkatkan Hasil Belajar Siswa dan Kemampuan Berfikir Kritis Siswa Pada Materi Rantai Makanan di Kelas V UPTD SD Negeri 5 Jeunieb - Azuryati Azuryati; Zahriyanti Zahriyanti (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to describe the implementation of the Project Based Learning (PjBL) model in improving students’ learning outcomes and critical thinking skills on the topic of food chains in Grade V at UPTD SD Negeri 5 Jeunieb. The study employed a descriptive qualitative approach with a field research design. The research was conducted during the 2025/2026 academic year. Data were collected through observation, interviews, and documentation, while data analysis was carried out through data reduction, data presentation, and conclusion drawing or verification. The results indicate that the implementation of learning using the Project Based Learning model on the food chain topic was carried out very well and in accordance with the PjBL syntax, which includes determining essential questions, designing the project, developing a schedule, implementing and monitoring the project, testing the results, and evaluating the learning experience. Observation results showed a learning implementation rate of 92.36%, categorized as very good. The application of the PjBL model also had a positive impact on improving students’ learning outcomes. This was evidenced by an increase in the number of students achieving learning mastery, from 6 students in the pretest to 11 students in the posttest. In addition, the PjBL model was effective in enhancing students’ critical thinking skills, with an average score of 75.00 in the good category. Students were able to identify problems, analyze relationships among living organisms in the food chain, express logical arguments, and draw conclusions based on observations and discussions. Therefore, the Project Based Learning model can be considered an effective alternative learning approach in elementary schools.